Comparison of Subjective Dizziness, Tinnitus, Headache, Taste, and Smell Results by Age Group in Yakumo Town Residents Health Checkup Conducted in 2019 with Measured Taste and Smell Test Results (Global Journal of Medical Research, 2023)
A self-administered questionnaire survey is conducted on various items related to health at the residents examination conducted in Yakumo Town Nikai-gun Hokkaido where population migration is small We will report on the results of the otolaryngology questionnaire survey conducted in 2019 The target population is 128 males and 169 females who are residents of Yakumo Town over 40 years old for a total of 297 people Self-administered questionnaire survey feeling conscious vertigo tinnitus headache hearing taste smell taste test Salt taste Salseve manufactured by Advantech and smell test 12 kinds of odors Smell sticks Daiichi Factory C0 Ltd
Keywords: yakumo study; olfactory function test; taste test; the prevalence of vertigo; the prevalence of tinnitus